Pengaruh Lama Fermentasi terhadap Karakteristik Minuman Probiotik Sari Buah Jambu Biji Merah (Psidium guajava L.) dengan Isolat Weissella confusa F213 - Ardi Ningsih Eka Putri, Ni Putu; Nocianitri, Komang Ayu; Wisaniyasa, Ni Wayan (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 11 No 3 (2022): Jurnal ITEPADO - 10.24843/itepa.2022.v11.i03.p14, 2022)
This research was aimed to determine the effect of fermentation time on the characteristics of red guava juice as probiotic drinks and to determine the right fermentation time that produced the best characteristics of product. Fermentation of red guava juice as probiotic drink used the Weissella confusa F213 isolates. This research used a Completely Randomized Design (CRD) with fermentation time as treatment factor, namely 0 hour, 12 hours, 24 hours, 36 hours, and 48 hours. Each treatment was repeated 3 times to obtain 15 experimental units. The data were analyzed by Analysis of Variance, and continued with Duncan Multiple Range Test (DMRT) if the treatment has a significant effect (P<0,05). The results showed that fermentation time affected on total LAB, total acid, pH, sour taste (score) and sweet taste (score), but had no effect on total sugar, hedonic of color, aroma, taste, and overall acceptance. The 12 hours fermentation time produced the best characteristics of red guava juice as probiotic drink, with: total LAB 9,35 Log CFU/mL, total acidity 0,09%, pH 4,15, total sugar 10,64%, the color was preferred, the aroma was slightly preferred, slightly sour and sweet taste were preferred, also overall acceptance was slightly preferred.